Workplace Happiness and Self-Efficacy as Correlates of Innovative Work Behaviour Among Mass Education Employees in Southwest Nigeria: A Mixed Method Approach - Waliyi Olayemi Aransi; Funmilola Elizabeth Akinyooye; Kamorudeen Taiwo Sanni; Olatunbosun Sunday Emmanuel Odusanya (Program Doktor Pendidikan FKIP Universitas Lampung, 2026)
The study explored workplace happiness and self-efficacy as correlates of innovative work behaviour (IWB) among mass education employees in southwest Nigeria using a mixed method approach. The study was motivated by the vital role of exhibiting IWB towards ensuring organisational resilience, effectiveness and sustainable performance. The study employed explanatory sequential mixed-method design, while multi-stage and purposive sampling procedures were used to select two-hundred and eight (208) mass education employees from five southwestern states, Nigeria. The study used Innovative Work Behaviour Questionnaire (α=0.86), Workplace Happiness Questionnaire (α=0.84), and Self-Efficacy Questionnaire (α=0.84), respectively, coulped with interview guide. Mean, standard deviation, regression and correlation analysis were used to analyse the generated data while responses from the interview were content analysed. The findings indicated that mass education employees maintained low level of workplcae happiness (x̄ = 2.33), and high self-efficacy (x̄ =4.05) towards organisation’s tasks. The results further revealed that workplace happiness (β = 0.255, t = 0.589, 0.005<.05) and self-efficacy (β = 1.597, t = 6.219, 0.000 <.05) had positive contributions to employees’ IWB. Results further revealed a significant positive moderately strong association between self-efficacy and IWB (r = .60, p < .001), but a significant positive weak association between workplace happiness and IWB (r = .30, p < .001). The study concluded that workplace happiness and self-efficacy determined mass education employees’ IWB. Employees should take ownership of their generated ideas, and be willing to promote them as well as recognise that workplace happiness is contagious in nature.